Fabrication and characterisation of tetrahedral amorphous carbon thin films - Li, Zhong (2010)
It is well known that diamond has an impressive set of properties that would make it an attractive material for many applications. However, there are some technical limitations to diamond synthesis. This has led to the development of a class of diamond related materials. This thesis reviews the history of the preparation of some diamond related materials. So far, the Filtered Cathodic Vacuum Arc (FCVA) technique has been reported to be an efficient method of producing high quality films. The Tetrahedral Amorphous Carbon (ta-C) film, which can be categorised as a kind of diamond-like carbon (DLC) film, is one of the most interesting films ever deposited by this technique. It is observed that more than 80% of the carbon atoms in this film form a random tetrahedral (sp3) network which results in some diamond-like properties.